Grain boundary properties of Tl-2212 and Tl-1223 thin films - Dark, C; Speller, S; Wu, H; Sundaresan, A; Tanaka, Y; Burnell, G; Grovenor, C (2005)
After more than 15 years active research, it is now clear that in YBCO grain boundaries act as severe weak links, and in order to produce YBCO thin films carrying high critical currents it is necessary to grow epitaxial films on appropriate substrates. We asked the question whether grain boundaries in thallium based superconductors cause the same degradation of properties, by adding to the very limited published data on the properties of grain boundaries in Tl-HTS systems. We have measured the properties of a statistically significant number of both 'artificial' grain boundaries on LaAlO 3, LSAT and SrTiO 3 bicrystal substrates and 'natural' grain boundaries in films grown on MgO substrates. The J c values of the bicrystal films are surprisingly high when compared to values for YBCO bicrystals, and for Tl-2212 were the same for 30° and 24° grain boundaries. The 'natural' grain boundaries showed two distinct type of electrical behavior, both with significantly higher J c values when compared to 'artificial' boundaries of similar misorientation. The J c values of the natural grain boundaries from the bi-epitaxial films show no decrease in J c with misorientation angle. The normalized values of J c for these Tl-2212 grain boundaries do not fall on the generic J c/θ trend line for YBCO boundaries. © 2005 IEEE.